BUKU KONTROL SHALAT SEBAGAI MEDIA HABITUASI SHALAT DI MI DIPONEGORO 03 KARANGKLESEM - Munasiroh Munasiroh (IAIN Purwokerto, 2018)
Abstract: This study uses descriptive qualitative field research methods. The locations studied were MI Diponegoro 03 Karangklesem, South Purwokerto District, Banyumas Regency. The research subjects included the fourth and fifth-grade teachers, fourth and fifth-grade students, fourth and fifth-grade parents, and the principal. The results of the study of the Shalat Control Book as a Media for Habituation of Prayers in Diponegoro 03 Karangklesem MI, South Purwokerto Subdistrict, Banyumas Regency, namely 1) In order to make the Book of Control Prayer effective, a collaboration between teachers and parents is needed to educate habituation prayer. 2) In the development of prayer control book media still, need evaluation. Evaluating the development of monthly prayer control books by class teachers, evaluating the effectiveness of the implementation of prayer control books by the madrasa head and the teacher council, and communicating the development of habituation prayer to parents. Keywords: control card, prayer, media, and habituation.